Broadband light and heat management with a self-regulating and user-controlled thermochromic smart window - Mitmit, Ceren; Mocan, Merve; Camic, B. Tugba; Cingil, Hande E.; Tan, Eric M. M. (Cell Press, 2023)
The energy demand for heating and cooling interior space contributes to rising global emissions. Windows are responsible for energy loss by heat exchange between the interior and outdoors. Scientists have been focusing on developing thermochromic materials for smart windows to modulate solar irradiation to reduce energy demand for interior comfort. Most studies show visible-light modulation when the temperature rises but fail to show privacy protection at night when the temperature drops. Here, we report a versatile user -controlled thermoresponsive window integrated with a transparent heater. The sandwiched poly(N-isopropylacrylamide) in a window enables powerless reversible transition between the transparent and opaque states at its activation temperature. The heater offers dual functionalities: a privacy switch to darken the window on demand and an extended spectral reflectivity in the infrared. A window that reflects heat helps reduce energy consumption for heating and cooling while preserving the transparency for visible light to illuminate the interior.
Keywords: Infrared-Spectroscopy; Hydrogel; Poly(N-Isopropylacrylamide); Pnipam; Films